Peranan Alumni Dalam Peningkatan Mutu Madrasah Di MTs Nurut Thullab Bangsal Kedungdung Sampang - Badruttamam Badruttamam; Nur Jamal; Muhammad Sholehuddin (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2023)
Alumni are one measure of improvement for improving the quality of education. As for several roles that can be performed by alumni in improving the quality of education, for example, contributing ideas to look for concepts and ways of working to improve the quality of education services, contributing to training or information needed by school residents, support morally and financially the needs and efforts of schools in improving quality, and so on. Based on this, there are two problems that are the main studies in this study, namely: First, what is the role of alumni in improving the quality of madrasas at MTs Nurut Thullab Bangsal, Kedungdung District, Sampang Regency, Madura?. Second, what are the supporting factors and inhibiting factors for the role of alumni in improving the quality of madrasas at MTs Nurut Thullab Bangsal, Kedungdung District, Sampang Regency, Madura?. In accordance with these problems, the researchers used a qualitative descriptive approach with the type of field research. The data collection procedures used in this study consisted of interviews, observation and documentation.